If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5p + 15 + 9 = 3p + -6 + 6 Reorder the terms: 15 + 9 + 5p = 3p + -6 + 6 Combine like terms: 15 + 9 = 24 24 + 5p = 3p + -6 + 6 Reorder the terms: 24 + 5p = -6 + 6 + 3p Combine like terms: -6 + 6 = 0 24 + 5p = 0 + 3p 24 + 5p = 3p Solving 24 + 5p = 3p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-3p' to each side of the equation. 24 + 5p + -3p = 3p + -3p Combine like terms: 5p + -3p = 2p 24 + 2p = 3p + -3p Combine like terms: 3p + -3p = 0 24 + 2p = 0 Add '-24' to each side of the equation. 24 + -24 + 2p = 0 + -24 Combine like terms: 24 + -24 = 0 0 + 2p = 0 + -24 2p = 0 + -24 Combine like terms: 0 + -24 = -24 2p = -24 Divide each side by '2'. p = -12 Simplifying p = -12
| 9m^2+8m=0 | | 3[b-4]=5b-2 | | 6/35-2/15= | | -7+8=2(y+8)-9y | | 3d-24-5=9d+18+1 | | 7*(9-11)+(5*2+2)/4= | | 5(-3-2x)=-15 | | 7x+5-4(x+1)=-2x+6 | | 25x^2+100x+64=0 | | -1+(-3y-3)=-4(7y-9)-2 | | 6[h+4]=-2h | | 9w-(4w-7)=38 | | 11j-11+15=11j+4 | | 4(2z+5)=5z+32 | | -2x-3=3x+17 | | h-27=-29 | | v=t(0)t^2-2t | | 0.15cm+1.15cm+2.051= | | 4(13-b)=6(2-0.5b) | | -1+5x=12-31x | | 3x-5=7x+55 | | 6x+9=-3 | | 5g+2(-4+2g)=1-g | | 6x^2+9x+12=0 | | -7x+8=-27 | | 4(x-8)=10 | | (4a-3b)(-2c)= | | 5x+17=2x+38 | | -7-7x=0 | | -12k+-48=60 | | 5x+21+7+15=24 | | 2-3(4-x)=5(2-x)+4x |